Frequency of Various Congenital Anomalies and Associated Maternal Risk Factors, an Experience at Tertiary Care Hospital - Javaria Aslam, Sadaf Khurshid, Sheeba Rehman, Shahnilah Zafar, Iram Aslam, Sara Gulbaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine frequency of congenital anomalies in children and associated risk factors of mothers. Setting: Department of obstetrics and gynecology Rai Medical College Sargodha. Study design: Descriptive observational study. Duration: July 2022 to December 2022. Methodology: All babies with congenital anomalies born within study duration and their mothers were included in this study. Anomalies of neonates were evaluated after proper clinical evaluation by a neonatologist. A questionnaire was designed to evaluate maternal risk factors. All collected data was analyzed using SPSS version 20. Results: Total 1900 babies delivered during this study period and out of them congenital anomalies were found in 31 (1.6%) cases. Most common anomaly was hydrocephalus in 10(32.2%) and meningomyelocele in 6(19.3%) cases. Most common maternal risk factor was consanguineous marriage in 15(48.3%) cases. Most commonly mothers with the age of 19-30 years were having babies with congenital anomalies. Practical Implication: This study helps us to understand the importance of avoiding consanguineous marriages, screening of high risk cases using various diagnostic techniques like ultrasonography during 16-20 weeks, use of folic acid supplements and in case of detecting congenital anomalies option of selective termination of pregnancy can be offered to the parents. Proper awareness of the parents and their counselling after birth of a baby with anomaly can prevent its recurrence in their future pregnancies Conclusion: Most common congenital anomaly reported in this study was hydrocapahlus followed by meningocele and most common maternal risk factor associated with these anomalies was consanguineous marriage. Keywords: Congenital anomaly, consanguineous marriage, Maternal risk factor, Neural tube defects